Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1175/jas3587.1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Oceanic Precipitation Efficiency in Cloud Models

Abstract: Precipitation efficiency is estimated based on vertically integrated budgets of water vapor and clouds using hourly data from both two-dimensional (2D) and three-dimensional (3D) cloud-resolving simulations. The 2D cloud-resolving model is forced by the vertical velocity derived from the Tropical Ocean Global Atmosphere Coupled Ocean–Atmosphere Response Experiment (TOGA COARE). The 3D cloud-resolving modeling is based on the fifth-generation Pennsylvania State University–National Center for Atmospheric Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 34 publications
0
62
0
Order By: Relevance
“…Although 2D and 3D model simulations show similarities in terms of collective thermodynamic feedback effects, vertical transports of mass, sensible heat and moisture, thermodynamic fields, surface heat fluxes, surface precipitation, precipitation efficiency, and convective and moist vorticity vectors (e.g. Tao and Soong, 1986;Tao et al, 1987;Grabowski et al, 1998;Khairoutdinov and Randall, 2003;Gao et al, 2004Gao et al, , 2005bGao et al, , 2007Sui et al, 2005;Zeng et al, 2007), the two types of simulations can also be different. One notable difference is the fact that 2D model simulations produce stronger convective cold pools than 3D model simulations do (Tompkins, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Although 2D and 3D model simulations show similarities in terms of collective thermodynamic feedback effects, vertical transports of mass, sensible heat and moisture, thermodynamic fields, surface heat fluxes, surface precipitation, precipitation efficiency, and convective and moist vorticity vectors (e.g. Tao and Soong, 1986;Tao et al, 1987;Grabowski et al, 1998;Khairoutdinov and Randall, 2003;Gao et al, 2004Gao et al, , 2005bGao et al, , 2007Sui et al, 2005;Zeng et al, 2007), the two types of simulations can also be different. One notable difference is the fact that 2D model simulations produce stronger convective cold pools than 3D model simulations do (Tompkins, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al (2004Gao et al ( , 2005bGao et al ( , 2007 showed that the vertical components of convective and moist vorticity vectors in both 2D and 3D frameworks highly correlate with the cloud hydrometeors. Sui et al (2005) revealed the similarities in precipitation efficiency between the calculations with grid data from both 2D model simulations of tropical squall lines with the Tropical Ocean-Global AtmosphereCoupled Ocean-Atmosphere Response Experiment (TOGA-COARE) forcing and 3D model simulations of typhoons without imposed forcing. Zeng et al (2007) showed that the relative humidity and cloud fraction produced by 2D model simulations are closer to observations than those generated by 3D model simulations.…”
Section: Model and Experimentsmentioning
confidence: 76%
“…The similarities include collective thermodynamic feedback effects, vertical transports of mass, sensible heat, and moisture, thermodynamic fields, surface heat fluxes, surface precipitation, precipitation efficiency, and convective and moist vorticity vectors (e.g., Tao and Soong 1986;Tao et al 1987;Grabowski et al 1998;Tompkins 2000;and Khairoutdinov and Randall 2003;Gao et al 2004Gao et al , 2005bGao et al , 2007Sui et al 2005). The differences include some differences between 2D and 3D model simulations, caused by the small model domain size in the 3D model, and the differences between 2D and 3D dynamics (Xu et al 2002), and high correlation of the horizontal and vertical components of dynamic vorticity vector with cloud hydrometeors, respectively, in the 3D and 2D frameworks because of the exclusion of dominant items in horizontal components of the 3D dynamic vorticity vector from the 2D framework (Gao et al 2005b;Gao 2008).…”
Section: Model Experiment and Rain Microphysical Budgetmentioning
confidence: 99%
“…The 2D model setup has been used to successfully simulate tropical rainfall (Li et al 1999), severe tropical storm and typhoon (Wang et al 2009;Yue et al 2009), and pre-summer heavy rainfall . Similar experiment data of TOGA COARE have been analyzed to study surface rainfall processes (Gao et al 2005a), precipitation efficiency (Li et al 2002a, Sui et al 2005, cloud merging (Ping et al 2008), diurnal variation of rainfall (Gao and Li 2010a), and effects of ice cloud on rainfall (Gao et al 2006). …”
Section: Model Experiment and Rain Microphysical Budgetmentioning
confidence: 99%